Tests of cold-formed high strength steel tubular sections undergoing web crippling. (15th June 2017) - Li, Hai-Ting; Young, Ben
Highlights: Cold-formed steel tubular sections with 0.2% proof stresses of 700 and 900 MPa were examined. A total of 65 web crippling tests was conducted. High strength steel tubular sections subjected to EOF, IOF, ETF, and ITF loading conditions were investigated. Existing codified web crippling design provisions are assessed. Abstract: This paper presents an experimental investigation of cold-formed high strength steel tubular sections undergoing web crippling. The tests were conducted on square and rectangular hollow sections of high strength steel with nominal 0.2% proof stresses of 700 and 900 MPa. The measured web slenderness values of the tubular sections ranged from 8.3 to 35.8. Tensile and compression coupon tests were conducted to obtain the material properties of the test specimens. The web crippling tests were conducted under the four loading conditions as specified in the North American Specification and Australian/New Zealand Standard for cold-formed steel structures, namely, the End-One-Flange, Interior-One-Flange, End-Two-Flange and Interior-Two-Flange loading conditions. It should be noted that the web crippling design provisions in these two specifications were mainly developed based on sections with web slenderness value greater than 40 and 0.2% proof stress less than 500 MPa. The test strengths obtained from this study were compared with the nominal strengths calculated from the North American Specification, Australian/New Zealand Standard and European Code for cold-formed steel structures. Furthermore, the test strengths were also compared with the nominal strengths calculated from the Australian Standard AS4100. Reliability analysis was performed to assess the reliability of the design provisions in the aforementioned specifications. Generally, it is shown that the nominal strengths predicted by the codified web crippling design provisions are either unconservative or very conservative. Hence, the existing codified design provisions are not appropriate for the cold-formed high strength steel square and rectangular hollow sections undergoing web crippling.